Sistem Pemantauan Level Keasaman dan Total Dissolved Solids Limbah Cair Berbasis Internet of Things (IoT) - Nizirwan Anwar; Agung Mulyo Widodo; Vitri Tundjungsari; Arief Ichwani; Kus Hendrawan Muiz; Yulhendri Yulhendri (Prosiding SISFOTEK, 2021)
Waste as the rest of artificial materials that have no utilization value, so at this time it is not utilized. Waste is often referred to as industrial waste, some consider it as crop residue. As indicated by PP No. 82 of 2001, liquid waste is the result of an action as a fluid. Liquid waste depends on its temperament, in particular the actual and total properties, metals, inorganic non-metals, natural totals, and microorganisms. Currently the world is facing a water crisis due to polluted waste. Some organizations are not rESPonsible for dumping their waste into the sea or waterways, depriving the oceans and rivers of their capacity. Waste that pollutes waterways can destroy the clarity of the water, thus making the water concentrated and polluted with various harmful microscopic organisms from the waste. Even the river cannot be used properly because it has been polluted by waste. So that wastewater does not pollute the environment and can still be reprocessed, it is necessary to monitor the level of acidity and the amount of dissolved minerals in the liquid waste. With the monitoring system, it will be known how high the acidity level in the waste is and whether the waste can still be processed and then used.